The Triz-Imen Method in the Intellectual Development of Children (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article examines the theoretical foundations and practical significance of the TRIZ-IMEN method as an effective pedagogical technology in the intellectual and creative development of children. The possibilities of applying this method in the preschool education process are analyzed, and its impact on children’s speech development, thinking skills, and intellectual potential is highlighted. In addition, the article reveals how the use of the TRIZ-IMEN method enables the organization of the educational process in an engaging, effective, and innovative manner.